A flexible working hydraulic system for mobile machines. Issue 2 (3rd May 2016) - Axin, Mikael; Eriksson, Björn; Krus, Petter
Abstract: This paper proposes a novel working hydraulic system architecture for mobile machines. Load sensing, flow control and open-centre are merged into a generalized system description. The proposed system is configurable and the operator can realize the characteristics of any of the standard systems without compromising energy efficiency. This can be done non-discretely on-the-fly. One electrically controlled variable displacement pump supplies the system and conventional closed-centre spool valves are used. The pump control strategies are explained in detail. Experimental results demonstrate one solution to the flow matching problem and the static and dynamic differences between different control modes.